EFECTIVIZACION DE LA PROHIBICION DEL TRABAJO INFANTIL TIPIFICADA EN LA LEY DE MINERIA, PREVIO A GARANTIZAR LOS DERECHOS FUNDAMENTALES DE LOS NIÑOS, NIÑAS Y ADOLESCENTES - Picoita Juárez, Aura del Cisne (2016)
The importance and transcendency of the partner-juridical problem of "Efectivización of the prohibition of the work infantile tipificada in the Law of Mining, previous to guarantee the fundamental rights of the children, girls and adolescents", the interest arose to study this thematic one due to the constant exploitation, abuse and vulneración of human rights to that you/they are subject the children, girls and adolescents that work in the handmade mining, being indispensable that the organisms of control of the work of those smaller than age are devoted to supervise the mining sectors, previous to control and to eradicate the infantile work, with the purpose of guaranteeing the rights to the education, health, worthy life; and, occur faithful execution to the prohibition of the work infantile tipifica in him Law of Mining and that at the present time they are inobservadas. The theoretical work and of field of the present thesis it allowed me to obtain approaches, with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of objectives, and contrastación of the outlined hypotheses, allowing to support the proposed changes. The content of the thesis is an intellectual effort of the postulante in the scientific and methodological environment that approaches theoretical and empirically, of the prohibition of the infantile work that is not guaranteed by the competent authorities, in the boy's benefit, girl and hard-working adolescent.